ANALISIS PENGARUH KEADILAN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA DAZZLE YOGYAKARTA - Fegi Pangestu Prayoga; Luluk Kholishoh; Rini Susilawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Human resources are an important asset of an organization, because they can determine whether or not the goals of the human organization are achieved. The organization will be able to realize its vision and mission properly with employees, because in the hands of employees all of that can be realized. This study aims to determine the effect of organizational justice and job satisfaction organizational citizenship behavior to Dazzle employees Yogyakarta. This is quantitative research. The population in this study were all 198 Dazzle Yogyakarta employees. While the sample used in this study as many as 50 employees. The sampling technique in this study was probability sampling using simple random sampling. Methods of data collection is done by using questionnaires and interviews. The data analysis technique used is multiple linear regression techniques supported by the t test, simultaneous test and the coefficient of determination. The data that has been obtained is processed using SPSS 21. The results of this study indicate that organizational justice1 has1 a1 positive1 and1 significant effect1 organizational citizenship1 behavior,1 job satisfaction has a positive and significant effect organizational citizenship behavior, organizational justice and job satisfaction together have a positive and significant effect organizational citizenship behavior, organizational justice, and job satisfaction jointly affect the organizational citizenship behavior of 63.9%, the remaining 36.1% is influenced by other variables not included in the research model